2010
DOI: 10.1021/ma1021715
|View full text |Cite
|
Sign up to set email alerts
|

Softening of PMMA Brushes upon Collapse/Swelling Transition. A Combined Neutron Reflectivity and Nanomechanical Cantilever Sensor Study

Abstract: In this work, we establish a direct correlation between chain mechanics and structural properties of polymer brushes upon swelling. We present experimental results on poly(methyl methacrylate) (PMMA) brushes prepared via surface initiated atomic transfer radical polymerization. Neutron reflectivity studies gave insight into the brush thickness and volume fraction profiles of the brush, gradually swollen with solvent mixtures. Comparison of our experiments with scaling theory yielded specific polymer-solvent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Upon complete swelling of the PDMAEMA brushes at pH 3, this spike in density profile disappeared, due to the contribution of counterions to the osmotic pressure. The collapse-swelling transition of PMMA brushes upon gradual addition of solvent mixtures also showed that osmotic pressure dominates over the enthalpy of polymer–solvent interactions . Not only can changes in pH lead to changes in the density profile of PDMAEMA brushes, but also changes in electric fields between brush substrates and parallel electrodes .…”
Section: Characterization Of Polymer Brushesmentioning
confidence: 98%
See 2 more Smart Citations
“…Upon complete swelling of the PDMAEMA brushes at pH 3, this spike in density profile disappeared, due to the contribution of counterions to the osmotic pressure. The collapse-swelling transition of PMMA brushes upon gradual addition of solvent mixtures also showed that osmotic pressure dominates over the enthalpy of polymer–solvent interactions . Not only can changes in pH lead to changes in the density profile of PDMAEMA brushes, but also changes in electric fields between brush substrates and parallel electrodes .…”
Section: Characterization Of Polymer Brushesmentioning
confidence: 98%
“…The collapse-swelling transition of PMMA brushes upon gradual addition of solvent mixtures also showed that osmotic pressure dominates over the enthalpy of polymer−solvent interactions. 869 Not only can changes in pH lead to changes in the density profile of PDMAEMA brushes, but also changes in electric fields between brush substrates and parallel electrodes. 892 In the latter case, PDMAEMA brushes were stretched nearly to their contour length at very high positive voltage, before being detached from the substrate.…”
Section: Neutron Reflectometry (Nr) and Small-angle Neutron Scatterin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular structure simulations conducted by Baulin and Halperin indicate monomer concentration dependence on c for thermoresponsive polymer brushes due to decreasing polymer volume fraction as the chains stretch away from the substrate [62]. Brush swelling experiments combined with surface stress measurements by Gutmann and coworkers indicate that free surface energy resulting from interfacial tension between solvent and brush significantly adds to the enthalpic and entropic energy contributions to c yielding more favorable mixing between elongated polymer brush chains and solvents than solution c values would predict [33]. This is contradictory to vapor sorption studies in polymer brushes [34] and polymer films [63], where the dominance on the entropic contribution to c makes its value much higher than predicted Hildebrand solubility parameters.…”
Section: Thermodynamics Of Polymer Brush Swellingmentioning
confidence: 99%
“…The application range of nanomechanical sensors has broadened in the last years, ranging from gas detection 4 , calorimetry 1,[5][6][7] , drug screening 8 , genetics 3,9 , proteomics [10][11][12] , microbiology 13,14 , glycomics 15 and metabolic measurements at the level of individual cells 16 , to cite just a few. A review of the chemicals and bioanalytes already detected by cantilever sensors states that nearly 50 analytes have been successfully detected 17 .…”
Section: Introductionmentioning
confidence: 99%